2020
DOI: 10.1038/s41598-020-78919-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of a mindfulness versus relaxation intervention on romantic relationship wellbeing

Abstract: There is increasing scientific interest in the potential association between mindfulness and romantic relationship wellbeing. To date, however, experimental studies using active control groups and testing dyadic effects (i.e. examining both actor and partner effects) are lacking. In the current study, romantically involved individuals engaged for 2 weeks daily in either guided mindfulness exercises, or guided relaxation exercises. Participants, and their partners, completed measures of relationship wellbeing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…Specifically, couples may benefit most from relational forms of mindfulness exercises, such as mindful awareness during shared activities and partner-focused loving-kindness meditation, rather than non-relational exercises such as sitting meditation and individual yoga. Research on couples-based mindfulness interventions is still in its infancy (Carson et al, 2004; Karremans et al, 2020), but our findings demonstrate the potential importance of targeted interventions. Further research should examine the differential effects of relational versus non-relational mindfulness exercises on relationship well-being.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Specifically, couples may benefit most from relational forms of mindfulness exercises, such as mindful awareness during shared activities and partner-focused loving-kindness meditation, rather than non-relational exercises such as sitting meditation and individual yoga. Research on couples-based mindfulness interventions is still in its infancy (Carson et al, 2004; Karremans et al, 2020), but our findings demonstrate the potential importance of targeted interventions. Further research should examine the differential effects of relational versus non-relational mindfulness exercises on relationship well-being.…”
Section: Discussionmentioning
confidence: 68%
“…Relationship mindfulness, by definition, is tied specifically to a given partner and romantic relationship context and may therefore be more strongly linked to PPR than general mindfulness (Kimmes et al, 2018(Kimmes et al, , 2020. Considering that in a recent study a general mindfulness intervention did not differ from a relaxation condition in improving relationship well-being (Karremans et al, 2020), understanding if a domain-specific type of mindfulness is more directly relevant to enhancing relationship quality over time may have implications for future intervention designs.…”
Section: Mindfulness May Promote Pprmentioning
confidence: 99%
“…Plus, although we randomized participants to conditions, we did not have a no-intervention control group, which limits our ability to draw causal conclusions. For instance, one recent study (Karremans et al, 2020) demonstrated that mindfulness training did not improve relationship well-being above and beyond an active control (relaxation training). Although the current research is concerned with different outcomes, we note here that future research is needed to replicate our findings with an active control that does not involve meditation of any sort.…”
Section: Discussionmentioning
confidence: 99%
“…Kappen et al (2018) conceptualize acceptance as "the ability and willingness to accept the partner's imperfections without feeling the urge to change the partner" (p. 1544), and have found acceptance to be a significant mechanism underlying the mindfulness-relationship satisfaction connection, especially for participants scoring low in trait mindfulness (Kappen et al, 2019). Likewise, Karremans et al (2020a), in a study involving romantic couples, confirmed the mindfulness-relationship satisfaction association and noted increases in relational quality and partner acceptance.…”
Section: Acceptance and Responsivenessmentioning
confidence: 90%